(untitled) (Swiss Medical Weekly, 2012)
Our complex healthcare systems are fragmented, and their functioning, both in terms of efficiency and quality, are plagued by multiple discontinuities. eHealth has the potential to ease transitions between the many settings and stakeholders of healthcare. eHealth can improve the continuity of healthcare information flow, can facilitate the re-engineering of care processes so that they become much more patient-owned and patient-controlled, and can enable better ways of accessing and producing care. Such capabilities evolve with the development of our information and knowledge-based society, reflected by the various generations of the world-wide-web. Starting with the “read-only Web” where the main task was to give access to health information, it has evolved into the “social Web” and provides support of patient-centred, collaborative care, and is reaching a stage where pervasive computing tools can intelligently partner with citizens to help them take better care of their health.